Effect of Fish Oil on Immune Response in Broiler Chicks Vaccinated Against IBD - Al-Mayah, Ali A.S. (International Journal of Poultry Science, 2009)
IBD can only be controlled by proper vaccination. The objective of this study was to determine the efficacy of an intermediate strain of live attenuated IBD vaccine in broiler chicks at 7th day of age, as well as the effect of fish oil on immune response in birds vaccinated with IBD vaccine. One hundred forty, day-old broiler chicks were reared and used for this purpose. The chicks were divided into 7 groups A, B, C, D, E, F and G. Groups A, B and C were vaccinated via drinking water route at 7th day whereas D, E and F were vaccinated at 14th day of age. Groups B, C, E and F were fed 50gm fish oil/kg diet for one week either before or after vaccination. Group G was acted as control. Three chicks from each group were sacrificed by decapitation one week interval from the first day until 28th day of age and bursa weight to body weight (Bursal index) was recorded at these periods. Blood samples were collected for detection IBD antibody titer using ELISA at all these periods from control group for detection MDA, whereas the blood has been collected from the treated groups at a period of seven days after vaccination until the end of the experiment at 28th day of age to detect the effect of time of vaccination and fish oil supplementation on the IBD antibody titer. On necropsy, the gross pathological changes were recorded. The changes were occurred after 7 days postvaccination. The affected bursa was edematous and covered with yellowish transudate, other showed pinpoint mucosal surface necrosis, whereas other undergo atrophy. The Bursal Index (BI) was gradually increased from 1st-28th day of age in the control group, whereas in group A it was increased from the 1st to the 7th day and decreased thereafter. In group D the index was increased from the 1st-14th day and decreased thereafter until the 28th day of age. The MDA of control group was decreased from the 1st to the 28th day. The antibody titer of group A was decreased in a way similar to that of the control group, but a significant (p